Temperature rise characteristics of C5F10O/CO2 gas mixture AC high voltage switch bus - Zhaoxuan Cui; Xin Lin; Xiaolong Li; Yalong Xia; Zhenxin Geng; Jianyuan Xu (High Voltage)
Abstract C5F10O/CO2 gas mixture is one of the most promising alternatives to SF6 as an insulating gas in high‐voltage switchgear. As a key performance index in product design, the temperature rise characteristics are rarely reported. In this paper, the thermodynamic parameters of C5F10O/CO2 gas mixture were calculated first. Then, the calculation model of transient temperature rise was constructed for a 252 kV/3150 A bus, and a temperature rise experimental platform was built to verify the reliability of the proposed calculation model. On this basis, the influence of different factors such as load current, charging pressure, mixing ratio, and structure size on the temperature rise of the bus was further analysed, and it is found that increasing the charging pressure and the mixing ratio of C5F10O could effectively reduce the bus temperature rise but it still could not reach the level of SF6. The main structure size that affects the temperature rise of the bus is the outer diameter of the conductor, which increases by 10.2%, and the temperature rise is the same as that of the original SF6 bus. Finally, a high‐precision bus temperature rise surrogate model, which combined with the Latin hypercube model, the coefficient of prognosis, and the Kriging fitting method was established to facilitate the structural design.